2014
DOI: 10.1590/1678-775720130643
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical properties of composites as functions of the syringe storage temperature and energy dose

Abstract: Objective:To investigate the mechanical properties of different classifications of composites indicated for posterior application as functions of the storage condition and of the energy dose.Material and Methods:Specimens (8x2x2 mm) were obtained according to the factors: I) Composites (3M ESPE): Filtek P60, Filtek Z350XT, and Filtek Silorane; II) Syringe storage conditions: room temperature, aged, oven, refrigerator, and freezer; and III) Energy dose: 24 J/cm2 and 48 J/cm2. After photoactivation, the specimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 20 publications
0
14
0
1
Order By: Relevance
“…This result could be associated with the AAA process, which consists the cycles application of heating and light, thus it may have increased the degree of C=C conversion of the resin luting agent, and hence its stiffness. Studies previous showed improved mechanical proprieties for some restorative composites after AAA (15,26), suggesting that the aging could have increased the modulus of the elasticity of the resin luting agent, consequently improving the ceramic strengthening as explained before. In addition, the σ 0 of the resin luting agent (axial position z=-t 2 ) for the ceramicresin specimens also was higher after AAA.…”
Section: Discussionmentioning
confidence: 66%
“…This result could be associated with the AAA process, which consists the cycles application of heating and light, thus it may have increased the degree of C=C conversion of the resin luting agent, and hence its stiffness. Studies previous showed improved mechanical proprieties for some restorative composites after AAA (15,26), suggesting that the aging could have increased the modulus of the elasticity of the resin luting agent, consequently improving the ceramic strengthening as explained before. In addition, the σ 0 of the resin luting agent (axial position z=-t 2 ) for the ceramicresin specimens also was higher after AAA.…”
Section: Discussionmentioning
confidence: 66%
“…where F is the maximum strength in N; L the distance between the rests; b the width of the specimen; h the height of the specimen; and F/Y the slope of the linear part of the stress–strain curve. 14…”
Section: Methodsmentioning
confidence: 99%
“…[ 6 7 ] Several studies concerning the storage stability of restorative dental biomaterials have been reported. [ 8 9 10 11 12 13 ]…”
Section: Introductionmentioning
confidence: 99%